PENINGKATAN KETERAMPILAN BERBICARA PADA MAHASISWA MELALUI PROGRAM SAMA SAVI (SATU MAHASISWA SATU VIDEO) - Ibda, Hamidulloh (Universitas Negeri Surabaya, 2019)
Student speaking skills are not all adequate and according to linguistic and non-linguistic rules. To speak correctly, well, and beautifully, recorded and uploaded on Youtube, students experience obstacles, such as being unfamiliar, afraid, insecure, and do not know linguistic aspects and non-linguistic aspects to speak right, good, and beautiful. In linguistic aspects consist of correctness of speech, placement of pressure, tone, joint, and relevant duration, diction / choice of words and accuracy of target speech. Whereas the non-linguistic aspects consist of calm, honest, and not rigid attitudes, views directed at followers, willingness to respect the opinions of others, proper gestures and gestures, sound loudness, fluency, relevance / reasoning, and mastery of topics. One Student, One Video (SAMA SAVI) program has been proven to improve the speaking skills of students of the Islamic Education (PAI) Study Program of STAINU Temanggung. Before the action, speaking skills in the aspects of linguistic and non-linguistic aspects of students were inadequate. After the actions of cycle I and cycle II, there was a significant increase in students? speaking skills, both from linguistic and non-linguistic aspects. In the process of implementing this program, researchers experienced seven obstacles as well as seven opportunities to improve speaking skills for students